PENGARUH VARIASI KONSENTRASI DAN DEBIT PADA PENGOLAHAN AIR ARTIFISIAL (CAMPURAN GREY WATER DAN BLACK WATER) MENGGUNAKAN REAKTOR UASB - Samudro, Ganjar; Syafrudin, Syafrudin; Yazid, Fauzia Rahmiyati (Universitas Diponegoro, 2012)
In this study Mixture of domestic grey water and black water were investigated. This Mixture consists of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), and Nitrate (NO3). This research investigated the influence of concentration and flow variation parameters to treating the Mixture Grey Water and Black Water. Effluent quality of decreasing concentration varied by the concentration and flow recorded BOD was about 102-544 mg/l, COD was about 287-1.230 mg/l, TSS was about 280-780 mg/l and for treating nitrate the result was fair enough than others was about 4-12 mg/l. According to the flow variation resulted the retention time are 4, 6 and 8 hours. The best effluent quality was happened 878 mg/LCOD, and varied by flow are 0,125. The results of research showed the higher concentration will decrease the value of BOD and Nitrate removal, due to the influence of pH.The higher flow will decrease the value of BOD and increase COD, TSS, and Nitrate removal, and optimum flow condition was 0,125 l/hour.